2001
DOI: 10.1128/jvi.75.19.9345-9356.2001
|View full text |Cite
|
Sign up to set email alerts
|

Localization to the Nucleolus Is a Common Feature of Coronavirus Nucleoproteins, and the Protein May Disrupt Host Cell Division

Abstract: The subcellular localization of transmissible gastroenteritis virus (TGEV) and mouse hepatitis virus (MHV) (group I and group II coronaviruses, respectively) nucleoproteins (N proteins) were examined by confocal microscopy. The proteins were shown to localize either to the cytoplasm alone or to the cytoplasm and a structure in the nucleus. This feature was confirmed to be the nucleolus by using specific antibodies to nucleolin, a major component of the nucleolus, and by confocal microscopy to image sections th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
238
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(255 citation statements)
references
References 63 publications
15
238
1
1
Order By: Relevance
“…An increasing number of virus proteins, including examples from retroviruses, DNA͞RNA viruses, and plant viruses, have been reported to exhibit nucleolar localization (9,22,(29)(30)(31)(32)(33)(34)(35). However, no specific function has been assigned to the nucleolar localization of any of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of virus proteins, including examples from retroviruses, DNA͞RNA viruses, and plant viruses, have been reported to exhibit nucleolar localization (9,22,(29)(30)(31)(32)(33)(34)(35). However, no specific function has been assigned to the nucleolar localization of any of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, more and more nonribosomal proteins including growth factors (Antoine et al, 1997;Galcheva-Gargova et al, 1998;Pederson, 1998a, b), virus proteins (Stauber and Pavlakis, 1998;Wurm et al, 2001) and regulators of apoptosis such as p53, DEDD, MDM2 and p14ARF (Stegh et al, 1998;Zhang and Xiong, 1999;Lohrum et al, 2000) were demonstrated to localize in this sub-nuclear organelle under certain conditions. It has been well documented that a cluster of basic amino acids could lead heterologous proteins into the nucleus/nucleolus (Kaffman and O'Shea, 1999), however, no consensus motifs have been characterized thus far for nucleolus targeting and the mechanism underlying nucleolar distribution still remains largely obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nucleolin has been known to participate in the packaging and shuttling of the ribosome between the nucleus and cytoplasm (13). There have also been numerous reports regarding the functional roles of nucleolin by forming large molecular complexes with other related factors, such as casein kinase (CK) II, c-Myb, midkine (MK), histone H1, nucleophosmin, p53, and protein phosphatase 1 (PP1) (14 -20), and then either directly or indirectly playing a role in the regulation of cell proliferation and growth, cytokinesis, replication, embryogenesis, and nucleogenesis (14,(21)(22)(23)(24). In addition to the many known functions of nucleolin, it may also function as a low affinity receptor of extracellular growth factor on the cell surface (25).…”
mentioning
confidence: 99%